PERAN LEMBAGA PEMASYARAKATAN DALAM PEMBINAAN KEMANDIRIAN BAGI NARAPIDANA KASUS NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS IIA BUKITTINGGI - Fitra, Romaidil; Basyarudin, Basyarudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Class IIA Bukittinggi Penitentiary is a correctional institution that conducts rehabilitation programs during incarceration to shape the character of inmates for their betterment in the future. This research explores the role of the Class IIA Bukittinggi Penitentiary in fostering self-reliance among inmates with narcotics cases, as well as the factors that hinder and support this rehabilitation process. Through a qualitative approach, this study collected data through documentation, interviews, and observations at the Class IIA Bukittinggi Penitentiary. The findings indicate that correctional institutions play a crucial role in providing self-reliance training to inmates, particularly in the context of narcotics cases, to prepare them for life after serving their sentences. However, there are several obstacles in implementing rehabilitation programs, including the lack of skills among supervisory staff in teaching relevant skills, as well as challenges in financing and providing adequate accommodation for a large number of inmates. Based on these findings, the study recommends that the Class IIA Bukittinggi Penitentiary enhance creativity and professionalism in providing self-reliance training, and offer relevant programs to equip inmates with the necessary skills to overcome challenges upon release. Implementation of these recommendations is expected to make correctional institutions more effective in rehabilitating inmates with narcotics cases and preparing them for reintegration into society.